Adaptive optimization technology of segmented reconstruction signal based on genetic algorithm for enhancing radar jamming effect - Wang, Yanqi; Wang, Chao; Shi, Qingzhan; Huang, Jingjian; Yuan, Naichang (Frontiers in Physics, 2023)
Given the improved capabilities of radar systems, addressing unfamiliar signals presents a challenge for radar jamming technology. To tackle this issue, this study proposes an adaptive technique for optimizing jamming waveforms to suppress multiple false targets in escort jamming scenarios. The objective is to minimize the detectability of false targets by fine-tuning phase modulation and individual waveform parameters. The optimization model adjusts the energy and delay of jamming waveform segments using intercepted radar signal phase modulation and direct forwarding. Realtime adaptation is achieved through the utilization of a genetic algorithm and radar constant false alarm rate detection based on received emissions. The key findings highlight the advantages of adaptivity in effectively suppressing false targets under diverse conditions. The technique successfully learns efficient waveforms through feedback, even without specific knowledge of the radar system. The optimized waveforms maintain consistent jamming impact across different constant false alarm rate settings, surpassing the limitations associated with fixed assumptions. The introduction of phase modulation enhances the resilience of false targets by creating noise-like characteristics. Remarkably, robust jamming is achieved with only 12 false targets, reducing complexity. The unified waveform design is particularly suitable for single platform jamming, eliminating the need for multiple jammers. Furthermore, the optimized waveforms demonstrate improved coverage of real targets under position errors. As a result, the approach exhibits versatility across various signals, processing methods, and scenarios. This study suggests that increased adaptability and the incorporation of machine learning techniques contribute to the advancement of radar jamming capabilities. By optimizing jamming waveforms, the adaptive approach presented in this study may enhance the effectiveness of countering advanced radar systems.